1988
DOI: 10.1007/bf01889028
|View full text |Cite
|
Sign up to set email alerts
|

Evacuation proctography: An investigation of rectal expulsion in 20 subjects without defecatory disturbance

Abstract: Evacuation proctography is a dynamic investigation of rectal expulsion that records the voluntary evacuation of thick barium paste on videotape. Evacuation is a passive phenomenon in a defined zone of the rectum, associated with pelvic floor descent of 3 cm from a resting position of the anorectal junction less than 2 cm above the plane of the ischial tuberosities. The anal canal does not open immediately; it takes about 4.5 sec to open to a maximum diameter of 1.5 cm, with rectal emptying in 11 sec. Anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(74 citation statements)
references
References 12 publications
4
68
1
1
Order By: Relevance
“…Dyssynergic defecation includes paradoxical contraction or the inability to relax the pelvic floor musculature resulting in a lack of descent of the pelvic floor, a failure to increase the ARA and potentially a prominent impression of the puborectal sling [3,5,11]. Although the decrease in the ARA during straining is considered a typical sign of dyssynergic defecation, other studies with conventional defecography could not confirm this finding [8], and other authors also found this sign in asymptomatic volunteers [26,27]. A recent study [16] on dynamic MR in paediatric patients with dyssynergic defecation described significant differences with regard to the ARA during straining and with regard to the ARA-change on straining between patients with dyssynergic defecation and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Dyssynergic defecation includes paradoxical contraction or the inability to relax the pelvic floor musculature resulting in a lack of descent of the pelvic floor, a failure to increase the ARA and potentially a prominent impression of the puborectal sling [3,5,11]. Although the decrease in the ARA during straining is considered a typical sign of dyssynergic defecation, other studies with conventional defecography could not confirm this finding [8], and other authors also found this sign in asymptomatic volunteers [26,27]. A recent study [16] on dynamic MR in paediatric patients with dyssynergic defecation described significant differences with regard to the ARA during straining and with regard to the ARA-change on straining between patients with dyssynergic defecation and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation in these patients may be due to personality parameters and stress. Also, structural abnormalities of the anorectum, such as rectocele and hidden rectal prolapse, are common in asymptomatic patients [16]. Examination and management of patients with severe constipation is often complicated and confusing, particularly in patients who demonstrate combined slow transit constipation and disordered defecation.…”
Section: Methodsmentioning
confidence: 99%
“…(27) Goei et al, 1989 (28) Shorvon et al, 1989 (29) Freimanis et al, 1991 (19) Mezwa et al, 1993 (18) Somers, 1994 (9) Ikenberry et al, 1996 …”
Section: Conclusãomentioning
confidence: 99%